Translating Tacit Medical Knowledge Into Explicit Knowledge - Iwai, Sachiko; Ishino, Fukuya (Journal of Knowledge Management Practice, 2009)
Cytological diagnosis is a method to detect cancer in which qualified specialists distinguish between cancerous and non-cancerous cells using an optical microscope. However, the medical knowledge used for diagnosis is tacit, which means that the result can vary depending on the education and experience of each qualified specialist (Tezuka F. 1991). In this study, the top 10% of specialists were first identified. Then their superior tacit knowledge was translated into explicit knowledge by the long-term collaboration of a top specialist and two amateurs who have no medical knowledge. This explicit knowledge was helpful for cytological diagnosis, even allowing amateurs to diagnose the cells. This translation of tacit knowledge into explicit knowledge allowed a manual to be created, which suggests that it may be possible to develop a computer program for cytological diagnosis.